PENERAPAN METODE PROFILE MATCHING UNTUK PREDIKSI PENERIMAAN MAHASISWA BARU (STUDI KASUS IDE LPKIA) - Andy Victor Pakpahan (Jurnal Komputer Bisnis, 2023)
New Student Admissions or PMB is the process of admitting new students carried out by universities regularly every time the new academic year arrives. PMB is carried out to recruit students every year, such as PMB at IDE LPKIA, new student registration data is used for higher education academic planning. PMB at IDE LPKIA experiences a difference between students who register and students who experience registration. In 2020 there were 154 prospective students, in 2021 there were 375 prospective students, and in 2022 there were 501 prospective students. Of the registrants each year, only a portion of the prospective students carried out the registration process, in 2020 there were 245 students, in 2021 there were 163 students, and in 2022 there were 265 students. The method used to search for gaps is Profile Matching, which is a method for comparing profiles and other profiles so that the results of differences in competence are known as gaps. The PMB that will be used is in 2023, namely 410 registrants, then the Profile Matching method is calculated which produces 277 registrant data which is concluded as registration. Based on the MAPE calculations carried out, the results of Profile Matching are included in category 3, namely forecasting at a sufficient level.